2019
DOI: 10.31729/jnma.4747
|View full text |Cite
|
Sign up to set email alerts
|

A Female with Right-Sided Thoracic Kidney with Bochdalek Hernia: A Case Report

Abstract: The thoracic kidney is the rarest form of an ectopic kidney that usually present on the left thoraxand twice more common in males. No case has been reported from Nepal and very few cases arereported worldwide. We report a 24 years-old female with right thoracic kidney with Bochdalekhernia diagnosed incidentally. We have included clinico-radiological and surgical findings of thecase with a review of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…A composite mesh was used in three patients (16%) [ 27 , 33 , 34 ]. One case did not report the type of mesh [ 35 ]. The suture type was mostly non-absorbable ( n = 13, 65%) followed by absorbable sutures ( n = 4, 20%).…”
Section: Resultsmentioning
confidence: 99%
“…A composite mesh was used in three patients (16%) [ 27 , 33 , 34 ]. One case did not report the type of mesh [ 35 ]. The suture type was mostly non-absorbable ( n = 13, 65%) followed by absorbable sutures ( n = 4, 20%).…”
Section: Resultsmentioning
confidence: 99%
“…Ioannidis et al reported a female having blunt abdominal trauma resulting in a right-sided diaphragmatic injury and protrusion of the right lobe of the liver in the thoracic cavity along with a fracture of the right lower ribs [ 12 ]. Other unusual presentations may include other abdominal organs in the thorax, as seen in a case report of Daha et al in which a 24-year-old female with a right thoracic kidney with Bochdalek hernia was diagnosed incidentally [ 13 ]. Korkut et al reported a 28-year-old female who presented with bowel obstruction and subsequently was found to have bowel necrosis at the time of emergency surgery, where small bowel and transverse colon herniated into the right-sided diaphragmatic hernia after a right laparoscopic hepatectomy due to a hepatic alveolar cyst 20 months ago [ 14 ].…”
Section: Discussionmentioning
confidence: 99%